23.5k views
1 vote
4x - 1
2.
= x + 7
Can someone help please?

User Sabalaba
by
5.3k points

2 Answers

2 votes

Answer:

19/3 =
6(1)/(3)

Explanation:


4x -12= x+7\\Collect-Like-Terms\\4x-x =7+12\\3x=19\\Divide -Both-Sides-Of-The-Equation-By ; 3\\(3x)/(3) =(19)/(3) \\\\x = (19)/(3)\\ \\x = 6.3\\

User Pharsfalvi
by
5.5k points
4 votes

Answer:

6
(1)/(3)

Explanation:

4x-12 = x+7

4x-12+12 = x+7+12

4x = x+19

4x-x = x+19-x

3x=19

x = 6
(1)/(3)

And if we substitute the value of x into the equation 4x-12 = x+7,

we will get 13
(1)/(3) = 13
(1)/(3) in the end.

Hope this helps :)

User Pat Murray
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.